2019
DOI: 10.5027/jnrd.v9i0.04
|View full text |Cite
|
Sign up to set email alerts
|

Clean Cookstove Technology Use for Energy Efficiency in the School System

Abstract: Globally, clean cookstoves represent the best substitute for open fire biomass stoves in order to reduce greenhouse gas emissions from fuelwood. Prospects to transfer this technology to Botswana are being explored. Our research objectives were to transfer the clean Institutional Cookstove (IC) technology to Okavango Research Institute (ORI), quantify the amount of mopane (Colophospermum mopane) fuelwood it consumes in comparison to the traditional biomass energy system, and analyze its potential to be used as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…They improve the taste and flavor of food and the quality of life [4][5][6]. Likewise, they help to manage demand and save energy by replacing conventional energy technologies [7], efficiently convert biomass into energy, emit very little smoke associated with complete combustion, and contribute to the sustainable use of scarce resources [8][9][10]. Switching to modern stoves and fuels and using ICS with better technological designs transforms lives by improving health, protecting climate and environment, empowering women, lowering households' expenses on medicines; reducing the workloads of women and children; and improving flexibility for women with regard to labor, time and money [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…They improve the taste and flavor of food and the quality of life [4][5][6]. Likewise, they help to manage demand and save energy by replacing conventional energy technologies [7], efficiently convert biomass into energy, emit very little smoke associated with complete combustion, and contribute to the sustainable use of scarce resources [8][9][10]. Switching to modern stoves and fuels and using ICS with better technological designs transforms lives by improving health, protecting climate and environment, empowering women, lowering households' expenses on medicines; reducing the workloads of women and children; and improving flexibility for women with regard to labor, time and money [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Padam et al [18] underlined the importance of providing incentives and arranging flexible payment systems and credit facilities. A study compiled by Mfundis and Commeh [7] indicated that socio-cultural, behavioral and competence-related barriers also make the adoption of ICS technology socially unacceptable at the household level. For example, youth in Botswana have made collecting fuel wood and making fire part of their culture.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation